Appraisal of Test Location and Variety Performance for the Selection of Tuber Yield in a Potato Breeding Program. Issue 5 (1st September 2015) - Paget, M. F.; Apiolaza, L. A.; Anderson, J. A. D.; Genet, R. A.; Alspach, P. A.
ABSTRACT: Differences in trait responses of genotypes across environments, or genotype × environment interactions (G × E), hinder the progress of genetic improvement. Characterization of these effects helps to determine breeding strategies and improve resource allocation in a cultivar development program. This study used historical multienvironment trial (MET) data (34 trials in five locations) for the analysis of marketable yield of advanced selections in a New Zealand potato ( Solanum tuberosum L.) breeding program. A factor analytic (FA) model was used for the analysis of these MET data. Contrasts based on the environmental loadings were observed between the program's main trial locations in the North Island (Pukekohe) and the South Island (Lincoln), indicating that these locations optimized differentiation between genotypes in terms of G × E effects. Genetic correlation estimates between trial environments were mostly moderately high (>0.5) to high (>0.8) and ranged from zero to positive with a maximum coefficient of 0.97, suggesting that quantitative (rescaling) rather than qualitative (crossover) G × E effects were of greater importance. A number of newly developed varieties were shown to have higher genetic yield potential than older and established commercial cultivars but did not necessarily show better yield stability over the locations tested.